Repeatability of methacholine challenge in asthmatic children measured by change in transcutaneous oxygen tension. - Phagoo, S B (1992)
BACKGROUND: The airway response to bronchial provocation may be evaluated by monitoring the fall in transcutaneous oxygen tension (PtcO2) but the repeatability of this method has not been rigorously assessed. METHODS: To determine the repeatability of this indirect method of assessment, bronchial challenge was performed with methacholine in nine children with stable asthma (age range 6-12 years) and was repeated 24 hours later. The response was determined by the fall both in forced expiratory volume in one second (FEV1) and in PtcO2. A modified tidal inhalation protocol was used in which quadrupling concentrations of methacholine were given, thereby reducing the time taken for the full challenge by almost half. The concentrations of methacholine that provoked a 20% decrease in FEV1 (PC20FEV1) and 15% and 10% falls in PtcO2 (PC15PtcO2, PC10PtcO2) were calculated. RESULTS: Repeatability measures, assessed as the 95% range for a single determination, were +/- 0.96 and +/- 1.12 doubling concentration differences respectively for PC15PtcO2 and PC10PtcO2 and +/- 0.80 for PC20FEV1. CONCLUSION: This challenge method using quadrupling concentrations and an indirect assessment of the response by PtcO2 was sufficiently repeatable for clinical use and compared favourably with repeated challenge assessed by FEV1. The PtcO2 method is simple and effort independent, and should prove particularly useful for measuring bronchial reactivity in young children.